Gastric bypass surgery does not increase the risk for sight‐threatening diabetic retinopathy. Issue 3 (31st August 2017) - Morén, Åsa; Sundbom, Magnus; Ottosson, Johan; Granstam, Elisabet
Abstract: Purpose: To study the occurrence and level of diabetic retinopathy (DRP) before and after planned bariatric surgery and to investigate potential risk factors for deterioration of DRP. Methods: The Scandinavian Obesity Surgery Registry (SOReg) was used to identify diabetic patients who underwent gastric bypass (GBP) surgery at three centres in Sweden during 2008–2010. Information regarding DRP screening was obtained from ophthalmological patient charts. Patients who had DRP screening before and after GBP surgery were included in the study. Results: The survey included 117 patients. Mean age was 50 (SD 10) years, body mass index (BMI) 43 (SD 8) kg/m 2 and HbA1c 64 (SD 18) mmol/mol before surgery. One year post‐GBP, BMI was reduced to 31 (SD 6) kg/m 2 . HbA1c was 43 (SD 10) mmol/mol, and in 66% (77/117) treatment for diabetes had been discontinued. Occurrence of DRP before GBP was as follows: no DRP 62%, mild 26%, moderate 10%, severe 0% and proliferative DRP 2%. No significant changes in occurrence of DRP after surgery were observed. Twelve patients (16%) developed mild DRP. In seven patients with pre‐existing DRP, deterioration was observed and two of these patients required treatment for sight‐threatening DRP. No association between preoperative BMI, HbA1c or reduction in HbA1c and worsening of DRP was found. Conclusion: In a majority of patients, no deterioration of DRP following GBP was observed. Screening for DRP before planned surgery is recommended for all diabetic patients about to undergo bariatric surgery to identify any pre‐existing DRP.